Surveillance of influenza A virus subtype H5N1 in a live bird market in Yangon, Myanmar: 2017–2018. Issue 6 (20th May 2020) - Thurain, Khin; Mon, Pont Pont; Nasamran, Chanakarn; Charoenkul, Kamonpan; Boonyapisitsopa, Supanat; Tun, Than Naing; San, Yin Yin; Aye, Aung Myo; Amonsin, Alongkorn
Abstract: A survey of influenza A viruses (IAVs) in the Mingalar Taung Nyunt live bird market (MTN‐LBM), Yangon, Myanmar, was conducted from December 2017 to December 2018. During the survey, 455 swab samples were collected from broilers, layers, backyard chickens and ducks from the MTN‐LBM. Ninety‐one pooled samples were screened for IAVs by real‐time RT‐PCR specific to the M gene. Positive pooled samples were individually retested for IAVs. In total, 2.63% of individual samples (12/455) were positive for IAVs. Out of 12 samples, seven samples from layer chickens and the environment were identified as IAV subtype H5N1. In this study, four IAVs were successfully isolated and further characterized by whole genome sequencing. Whole genome sequence analysis revealed that the viruses were characterized as highly pathogenic avian influenza virus subtype H5N1 (HPAIV‐H5N1) of clade 2.3.2.1c. Phylogenetic and genetic analyses showed that Myanmar HPAIV‐H5N1 was closely related to HPAIV‐H5N1 clade 2.3.2.1c isolated from China and Vietnam in 2014. Our results suggested that the live bird market in Myanmar represents a significant risk of HPAIV‐H5N1 transmission in poultry and humans. Moreover, HPAIV‐H5N1 clade 2.3.2.1c is widely distributed in South‐East Asia including Myanmar.